Presence of detrusor muscle in bladder tumor specimens—predictors and effect on outcome as a measure of resection quality - Shoshany, Ohad; Mano, Roy; Margel, David; Baniel, Jack; Yossepowitch, Ofer (Urologic oncology, 2014)
To identify predictors of the absence of detrusor muscle in bladder tumor specimens and analyze its effect on clinical outcome as an indicator of resection quality. The bladder cancer database of a tertiary medical center was queried for patients who underwent complete transurethral resection of bladder tumor (TURBT) between 2008 and 2009. Study end points were absence of detrusor muscle in the surgical specimen and its association with disease recurrence/progression. Detrusor muscle in the surgical specimen was found in 265 of the 332 study patients (79%). The likelihood of finding muscle increased with higher clinical stage (Odds Ratio [OR]-1.8), higher tumor grade (OR-3), larger tumor size (OR-3.2), multifocal disease (OR-1.7), and nonpapillary morphology (OR-2.3). History of bladder cancer, surgeon's experience, and tumor location in the bladder had no effect. In the whole study population, neither tumor recurrence nor disease progression was associated with absence of detrusor muscle. In patients with T1 tumors, absence of detrusor muscle in the specimen was associated with higher early recurrence rate but not worse long-term outcome. Absence of detrusor muscle in TURBT specimens is not determined by the technical difficulty of the procedure or surgical experience. Surgeons are more prone to obtain deep muscle in large, nonpapillary-appearing tumors, likely reflecting efforts to attain accurate staging in these cases. The presence or absence of detrusor muscle may serve as a surrogate of resection quality in patients with T1 tumors, but its general applicability to the overall population of patients undergoing TURBT remains questionable.